Policy innovation to enhance access to universal health coverage: A case of Kota Semarang - Hanani Retna; Santoso R. Slamet; Astuti Retno Sunu; Djumiarti Titik; Priyadi Budi Puspo (E3S Web of Conferences)
Achieving Universal Health Coverage (UHC) has been a policy priority globally including in Indonesia. To achieve UHC, government needs concerted efforts at all levels, from central government to district governments. The efforts at district level government are particularly important in Indonesia as health care is one of decentralized government functions that has to be managed and financed by district government. Under such context, this article analyses the implementation of PANDANARAN program in Kota Semarang. Kota Semarang has been successful in achieving UHC where approximately 95.37 percent of its population is now covered by the National Health Insurance (JKN) program. This success is partly supported by PANDANARAN program in which citizens can directly reporting barriers to access UHC to the Health Office. As a result, this program has successfully improved access to UHC in Kota Semarang. The incremental nature of PANDANARAN is also a suitable response from the government to fill the existing UHC coverage gap. Policy implication that needs to consider is to create substantive transformation in its policy design to ensure sustainability of the program.